Is intergenerational care associated with depression in older adults? - Han, Shurong; Guo, Jiahui; Xiang, Jianjun (Frontiers in Public Health, 2024)
Background It has become an alarming issue that older adults in China are facing mental health issues, causing severe depression. In this context, intergenerational care, in which grandparents care for young children instead of the young parents, is gaining importance. This study aims to explore the correlation between intergenerational care and depression among older adults, seeking alternative approaches to enhancing their quality of life. This study concludes that intergenerational care is an effective strategy for promoting active aging. Methods This study used multiple linear regression, propensity score matching, and additional analysis of heterogeneity, mediation, and moderation effects, with data from the 2018 CHARLS survey. Results The results indicated a negative correlation between intergenerational care and depression among older adults. The correlation was stronger for females and younger older adults people. Additionally, social activities served as a mediator between intergenerational care and depression among older adults, and health satisfaction positively moderated this relationship. Conclusion This study posits that intergenerational care serves as an effective approach for promoting active aging. It emphasizes the necessity for supportive government policies and community-family collaborations to encourage intergenerational care and its beneficial impact on mental health among older adults.